Digital visual effects (DVFx): comparative iconography analysis in Malaysian, Indian and Australian Award-Winning Movies - Hasrul Hashim (Penerbit Universiti Kebangsaan Malaysia, 2020)
This aim of this article is to investigate the usage trends of DVFx technology in Malaysia, India and Australia’s film industries. DVFx is also called creative support tools or CST. The variety of CST forms used in the production of most films has changed the landscape of production and post-production in Malaysia, India and Australia. Eleven films from those countries that have been awarded the best visual effects in local film festivals were selected as a sample to compare the trends in DVFx usage in those countries. Images and digitally generated scenes were analysed and have revealed a new level of digital creativity in the film industry. The iconographic analysis is divided into three categories based on the function of DVFx usage. These functions comprise the construction of ‘fantasy’, creative simulation and storytelling support, and visual enhancement and corrections. This study also found that the design structure is the most crucial element in a film. DVFx is used in the creation of fantasy elements through the creation of characters, settings and props. DVFx has also been used to reinforce the storyline by stimulating creativity through the creation of spectacular action scenes. DVFx have also acted as a visual enhancement tool through the animated design of the opening titles and transition scenes.